DAMPAK PENAMBANGAN PASIR TERHADAP LINGKUNGAN DI DESA OHIODERTUTU KECAMATAN KEI KECIL BARAT KABUPATEN MALUKU TENGGARA - Welhelma Remetwa; Selvana T. R. Tewal; Kalvin Salindeho Andaria (Jurusan Pendidikan Geografi Universitas Negeri Manado, 2021)
The study describes the impact of sand mining on the environment in Ohoidertutu Village, West Kei Kecil District, Southeast Maluku Regency. The research method used is a qualitative method with a descriptive approach. The results that the realization of sand mining in Ohoidertutu Village affected people's lives and even caused environmental damage and pollution. The research results explain 1) ownership of mining land is not clear, 2) sand mining does not have a permit, 3) the amount of the market price of sand so that mining is carried out without considering the impact on people's lives and the environment, 4) the condition of the mining area is very apprehensive, 5) sand mining is disturbing the existence of the community, 6) the village government is part of the sand mining, 7) the socio-economic existence of the community is disturbed by the loss of land and agricultural products, 8) sand mining hurts a negative impact on environmental damage and even pollution, loss of forest ecosystems, land and agricultural products, flooding, landslides and even disease outbreaks, 9) handling is still in the planning stage by the village government, and 10) solutions to closing mining land, hoarding, planting trees, cooperating with both the private sector and local governments.